Theoretical Prediction and Experimental Determination of Vapour-Liquid Equilibrium for Ternary Systems Trimethyl Borate-Methanol-N,N-Dimethylformamide/N,N-Dimethylacetamide - Bao, Zhenyu; Zhang, Weijiang; Cui, Xianbao; Xu, Jiao (Asian Journal of Chemistry, 2015)
Vapour-liquid equilibrium prediction of ternary systems: trimethyl borate-methanol-N,N-dimethylformamide and trimethyl borate-methanol-N,N-dimethylacetamide were conducted through combined utilization of Materials Studio, COSMO-SAC program and ChemCAD. The vapour-liquid equilibrium data obtained were compared with the experimentally measured data. Results showed that predicted values were comparatively conservative than measured ones, which indicated better performance of solvents can be achieved actually. Measured data were correlated using three frequently used activity coefficient models, of which binary interaction coefficients were obtained. The solvents displayed obvious solvent effect, especially N,N-dimethylacetamide. This proves the validity of N,N-dimethylacetamide as an effective solvent.